Sustained Endocytosis Inhibition via Locally‐Injected Drug‐Eluting Hydrogel Improves ADCC‐Mediated Antibody Therapy in Colorectal Cancer - Chong Wu; Xiaoting Liu; Rong Liu; Shiyao Song; Zi‐Fan Zheng; Yilin Zeng; Yong Mei; Jing‐Yang Zhang; Qijia Duan; Run Lin; Jin‐Zhi Du; Weiling He (Advanced Science)
Abstract The epidermal growth factor receptor (EGFR) is a validated therapeutic target for RAS/RAF wild‐type colorectal cancer (CRC). However, monoclonal antibody‐based anti‐EGFR therapies such as cetuximab have limited effectiveness. Herein, it is identified that EGFR internalization is associated with poor treatment response and prognosis in patients with CRC, based on a retrospective analysis of patients treated with cetuximab. It is further demonstrated that the endocytosis inhibitor prochlorperazine (PCZ) can move EGFR, which is hidden inside the cell, to the cell surface to improve therapeutic antibody binding. Thus, a thermosensitive hydrogel co‐loaded with cetuximab and PCZ (Gel@Cmab/PCZ) is constructed for sustained inhibition of endocytosis and effective cetuximab delivery. Peritumoral injection of Gel@Cmab/PCZ shows strong antitumor efficacy in subcutaneous and orthotopic CRC tumor models and completely abrogated liver metastasis when combined with chemotherapy. In a humanized patient‐derived xenograft model, a single injection of Gel@Cmab/PCZ with one‐third of the conventional cetuximab dose achieved 91% tumor growth inhibition, which promoted NK cell infiltration into tumor tissues and their antibody‐dependent cell‐mediated cytotoxicity effect. This study represents a novel strategy to boost the monoclonal antibody‐mediated anti‐tumor response in CRC.